THE IMPACT OF ACADEMIC WORKLOAD ON STRESS LEVELS AND PROCRASTINATION AMONG FIRST-SEMESTER UNIVERSITY STUDENTS - Rizki Dwi Wahyuni (CV Grasta Glory, 2025)
The early stage of college is a crucial transitional period for new students, marked by the need to adjust to the higher education learning system. During this phase, first-year students often face a heavy academic workload, which can significantly affect their psychological well-being. This study aims to describe the impact of academic workload on stress levels and procrastination tendencies among early-semester university students. This research adopts a descriptive qualitative approach, utilizing open-ended questionnaires distributed online via Google Forms for data collection. The participants were first- and second-semester students selected through purposive sampling. The findings reveal that most students feel overwhelmed by the quantity and complexity of assignments. This contributes to heightened academic stress, as indicated by symptoms such as mental fatigue, anxiety, and decreased motivation to study. Furthermore, unmanaged stress was found to lead to procrastination behaviors, serving as a coping mechanism to avoid academic pressure. Therefore, educational institutions must play an active role in providing psychosocial support and time management training to help prevent the long-term negative effects on students' mental health.